Management of ring spot disease of papaya through plant products - SHYAM SINGH, L.P. AWASTHI* and (Indian Phytopathology, 2009)
The most effective treatment, to prevent papaya ring spot disease of papaya was ten sprays with aqueous root extract of Boerhaavia diffusa along with milk protein.It exhibited minimum (20.18, 20.65 %) papaya ring spot disease incidence followed by five sprays with B. diffusa along with milk protein + five sprays with aqueous leaf extract of Clerodendrum aculeatum along with milk protein (23.67, 24.23 %) and ten sprays with C aculeatum along with milk protein (28.13, 29.12 %) during 2004 – 05 and 2005 – 06, respectively. Maximum plant height, number of fruits, fruit yield per plants and minimum yield losses were observed in papaya plants given ten sprays of B. diffusa along with milk protein followed by five sprays with B. diffusa along with milk protein + five sprays with C aculeatum along with milk protein and ten sprays with C. aculeatum along with milk protein in all the varieties during both years.